Adhesive Capsulitis of Shoulder (Frozen Shoulder) among the Diabetic Patients with Rheumatic Complaints (Medicine Today, 2020)
Introduction: Adhesive capsulitis of shoulder is the most common soft tissue rheumatism among the diabetes patients with rheumatic complaints but the etiology is still unknown. To detect the incidence of adhesive capsulitis (frozen shoulder) among diabetic patients with rheumatic complaints.Materials and Methods: All patients having diabetes with rheumatic complaints attended in the department of Physical Medicine and Rehabilitation, BIRDEM and BSMMU, Dhaka during the period June 2003 to November 2003 were included in this study.Results: After discarding unsatisfactory samples, 273 samples were assayed for study. Out of 1665 patients 273 (16.40%) had adhesive capsulitis. Out of 273 patients 145 (53.12%) were female and 141 (51.65%) were housewives and of 206 (75.45%) patients was in age group 41-60 years.Conclusion: The incidence of adhesive capsulits of shoulder among diabetic patients female is more than male. It is found that housewives and elderly people are mostly sufferer with this disease.Medicine Today 2020 Vol.32(1): 67-69